Reckless : living shadows - Funke, Cornelia, 1958- (Funke, Cornelia, 1958- Reckless (Series)., 2016)
Jacob Reckless journeys to the Mirrorworld to tell his shapeshifting friend Fox that a fairy curse--a deadly moth in his chest--means he has only one year to live.